A rare case report of pancreatic low-grade fibromyxoid sarcoma (LGFMS) - Eric J. Weiler; Thomas Murickan; Crystal N. Drayer; Sajjaad H. Samat; Michael A. Kia (Surgical Case Reports)
Abstract Background Low-grade fibromyxoid sarcoma (LGFMS) is an uncommon neoplasm generally affecting muscle tissue. It presents rarely in abdominal viscera and even more rarely occurs in the pancreas. All types of pancreatic sarcomas are uncommon, and LGFMS is a rarer still. We present the case of an LGFMS in the pancreas. Because of its rarity, there are no guidelines for appropriate treatment or summations of the natural course of this illness. Case presentation We present the case of a 49-year-old female who presented with epigastric pain. She had a prior history of three episodes of acute pancreatitis many years earlier. A CT revealed a pancreatic body mass, which was biopsied. Pathology returned LGFMS. The patient underwent a distal pancreatectomy and splenectomy. She did well after the case and did not require further intervention. Conclusion Though it is exceedingly rare, cases of pancreatic LGFMS should be reported in order to guide clinical decisions. LGFMS has been shown to have high malignant potential in other tissues, and there is no reason to think pancreatic masses will be different. By building a body of evidence about these rare tumors, patient care will benefit.